Eficiência na administração pública em tempos de austeridade: estudo de casos múltiplos - Souza, Simone de (2022)
The New Tax Regime, instituted by Constitutional Amendment No. 95/2016, attempts to reverse the acute fiscal imbalance in which the Federal Government finds itself, due to an unprecedented increase in public debt in recent years. To this end, it established the spending cap rule that consists of freezing public spending, in real terms, for all federal agencies, for at least ten years, starting in 2017, this being a government bet to recover the confidence of the investors and the country's economic growth. However, for the New Tax Regime achieve its purpose, constant decreases in discretionary expenses will be necessary to compensate the increase in mandatory expenses, in order not to break the ceiling established by it. This will be a great challenge for public agencies, which need to remain efficient, even with the imposition of budgetary restrictions. Given this scenario, the objective of this study is to identify, through multiple case studies in public agencies (MPF and TCU), using the mixed research method (quantitative and qualitative), which measures have been taken to face the spending ceiling and that can be maintained over the long term. The results of the quantitative survey confirmed the growth of mandatory expenses over discretionary expenses of the agencies analyzed in the post-NRF period. It was also confirmed that investments were the most affected expenses, with minimum budget participation records. In the qualitative research, it was possible to identify the main responses of public agencies to moments of crisis: expenditure cuts and efficiency gains. In relation to the first, the main and most substantial cut measure identified was the decrease in cost expenses due to the decrease in the number of properties or the decrease in their size. that is, there is a reduction in the physical structures of public administration. In addition, the containment of personnel expenses, such as the freezing of hiring and wages, proved to be worrying, as it can affect the productivity of employees and compromise the provision of services over time. As for the second, the measures of efficiency gains that deserve to be highlighted are investments in IT, cooperation and partnership between public bodies, the expansion of teleworking and organizational redesign. Finally, it was possible to conclude that achieving efficiency in public administration, in a context characterized by budget constraints and digital transformation, will certainly demand innovative solutions from public agencies, through substantial changes in their forms of organization and provision of services.